2006
DOI: 10.2169/internalmedicine.45.0163
|View full text |Cite
|
Sign up to set email alerts
|

Abducens Nerve Palsy and Ipsilateral Incomplete Horner Syndrome: A Significant Sign of Locating the Lesion in the Posterior Cavernous Sinus

Abstract: It is a rare combination of neurological manifestations to have abducens nerve palsy and ipsilateral incomplete

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, incomplete Horner's syndrome without anhydrosis, as in the case reported here, indicates the involvement of the periarterial sympathetic plexus at the third angulation point [17]. To date, only 13 cases with this combination of symptoms secondary to metastatic neoplasm within the cavernous sinus have been reported [4,10-16]. Regarding the primary lesions in these cases, there were 1 small cell lung cancer [10], 1 parotid cancer [10,12], 1 breast cancer [11], 1 gastric cancer [10], 1 uterine cancer [4], 3 undetermined origins [13,14] and 3 nasopharyngeal cancers [15].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Furthermore, incomplete Horner's syndrome without anhydrosis, as in the case reported here, indicates the involvement of the periarterial sympathetic plexus at the third angulation point [17]. To date, only 13 cases with this combination of symptoms secondary to metastatic neoplasm within the cavernous sinus have been reported [4,10-16]. Regarding the primary lesions in these cases, there were 1 small cell lung cancer [10], 1 parotid cancer [10,12], 1 breast cancer [11], 1 gastric cancer [10], 1 uterine cancer [4], 3 undetermined origins [13,14] and 3 nasopharyngeal cancers [15].…”
Section: Discussionmentioning
confidence: 79%
“…However, when both are present, it is important to localize the site of the lesion [16]. When these rare clinical features are manifested, we have to consider paratrigerminal syndrome or a lesion of the posterior cavernous sinus [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the cavernous sinus, the oculosympathetic fibers coalesce and run in close proximity to the sixth cranial nerve. Thus, the combination of an ipsilateral sixth nerve palsy and a postganglionic Horner's syndrome is highly suggestive of a cavernous sinus lesion [35][36][37][38]. Tsuda et al [36] reported nine patients with this clinical combination.…”
Section: Postganglionic Horner's Syndrome (Third-order Neuron Lesions)mentioning
confidence: 99%